Fostering creativity in language classes: Needs and challenges in the digital age - Hafizoah, Kassim; Ramiaida, Darmi; Zulfa, Sakhiyya (Penerbit UMPSA, 2024)
This paper explores the importance of fostering creativity in language classes in the current and digital world, addressing both the needs and challenges of incorporating creative practices into language instruction. As one of the 21st century skills, the augmentation of creativity in the educational settings is crucial as creativity enhances engagement, critical thinking, and communication skills. These skills are essential not only for language acquisition and retention, but also for survival in the professional settings. We discuss the transformation of language education and the placement of creativity in this evolution. The value of encouraging creative activities and strategies for language instruction and in language classes, empowered by technology and artificial intelligence are highlighted. However, implementing creative approaches faces several challenges, including limited teacher training and lack or resources. To enable creativity in technology-integrated language classes, we therefore, advocates for a balanced integration of creativity with contemporary and conventional approaches, highlighting the need for flexible frameworks, professional development, and the use of digital tools to support innovative, learner-centred language teaching.